Sistem Pendukung Keputusan Pemilihan Guru Baru Pada Jurusan Jaringan Komputer Dengan Menggunakan Metode SMARTER - Slamat Karunia Putra Daeli (Bulletin of Information System Research, 2023)
The teacher is a person who is responsible and responsible for the education of his students, either individually or classically, at school or outside of school. In the process of selecting a new computer network teacher (TKJ) at SMK Amir Hamzah Medan still not using a decision support system that can facilitate SMK Amir Hamzah Medan in choosing a computer network teacher (TKJ) who is professional in their field because at this time the selection of teachers at SMK Amir Hamzah is still based on interviews and testing of the ability of prospective teachers at SMK Amir Hamzah. However, there is still no specific reference used to determine who will be accepted as a network teacher at SMK Amir Hamzah based on the results of interviews and tests conducted.